PENGARUH KEMAMPUAN MEMBACA PEMAHAMAN TERHADAP HASIL BELAJAR SISWA MELALUI PEMBELAJARAN BAHASA INDONESIA KELAS IV DI SD NEGERI KADUAGUNG - Yani Suryani Cahyanigrum; Neng Lia Yulianengsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of this research is to investigate how learning Indonesian language impacts the reading comprehension abilities of fourth-grade students at Kaduagung Public Elementary School who are the subjects of this study. A quantitative approach is used for the design of a Pre-Experiment, specifically the One Group Pretest-Posttest design. Data was collected through reading comprehension ability tests (Pretest-Posttest), and tests for normality, homogeneity, and hypothesis (t-test) were used for analysis. The research results indicate that students' reading comprehension abilities significantly improved before and after learning Indonesian language. The average score of students' reading comprehension abilities increased significantly after the start of Indonesian language learning, showing that reading comprehension abilities have a positive impact on students' learning outcomes. Therefore, this research provides important implications for teachers and parents to enhance their students' reading comprehension abilities.